2013
DOI: 10.1186/1756-9966-32-3
|View full text |Cite
|
Sign up to set email alerts
|

High expression of IL-17 and IL-17RE associate with poor prognosis of hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a typical malignancy in a background of chronic inflammation. Th17 cells (a major source of IL-17) constitute crucial components of infiltrating inflammatory/immune cells in HCC and can amplify inflammatory response via binding to interleukin-17 receptor (IL-17R). Thus, we investigated the expression and clinical significance of IL-17 and IL-17 receptor family cytokines in HCC.MethodsThe expression and prognostic value of IL-17 and IL-17R (A-E) were examined in 300 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 38 publications
6
118
0
Order By: Relevance
“…A recent study also found that high expression of IL-17 and IL-17RE associated with poor prognosis of hepatocellular carcinoma (28). IL-17A has also been found to promote hepatocellular carcinoma metastasis via MMP2 and 9 expression (29).…”
Section: Discussionmentioning
confidence: 94%
“…A recent study also found that high expression of IL-17 and IL-17RE associated with poor prognosis of hepatocellular carcinoma (28). IL-17A has also been found to promote hepatocellular carcinoma metastasis via MMP2 and 9 expression (29).…”
Section: Discussionmentioning
confidence: 94%
“…The present study also observed that serum IL-17, IL-8 and IL-6 levels were increased in HCC patients compared with those in the healthy control group, but the design of this study did not provide an opportunity to determine the underlying mechanisms for such increases. However, it has been reported that increases in the number of Th17 cells in HCC patients, which occur concurrently with increases in serum IL-17 levels, are associated with decreases in overall survival and disease-free survival time (28,29). Additionally, Park et al (30) reported that anticancer drugs can induce IL-8 secretion and the expression of IL-8 receptors on liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…CLL D chronic lymphocytic leukemia; AC D adenocarcinoma; CRC D colorectal carcinoma; HCC D hepatocellular carcinoma; NA D not applicable or not mentioned in the article; NSCLC D non-small cell lung carcinoma. 15,16,[18][19][20]30,37,[40][41][42][43][44][45][46][47][48][49][50] Five studies reported on a correlation between a high number of IL-17 C cells and improved survival. 21,28,29,51,52 It is important to note that in two of these five studies, the IL-17 C cells were scored in areas with the densest lymphocytic infiltrate, one of which was on pancreatic ductal adenocarcinoma patients who had received immunotherapy (the correlation between IL-17 and survival was based on 12 patients).…”
Section: Study Design and Selection Criteriamentioning
confidence: 99%